(untitled) (Journal of Pedagogical Inventions and Practices, 2024)
Under the influence of new curriculum, physical education is standards have been effective changes, but due to the impact of teaching philosophy in the traditional sense, to promote sports teaching, whether in content or applied teaching, there are some problems. Therefore, in the actual development, teachers should not only focus on students’ physical education, but also into the aesthetic education in Physical Education. This article has pay attention to PE teaching aesthetic education methods for resolution.